EVALUATION OF THE APPLICATION OF GOOD MANUFACTURING PRACTICE AND SANITATION STANDARD OPERATING PROCEDURES IN PRODUCTION PROCESS - Candrianto, Candrianto; Mouludi, Isra; Sipahutar, Erwinsyah (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
This study aims to evaluate the application of the basic requirements of food safety standard, namely GMP and SSOP during the production process. The observations method for data collection in this study was through interviews of workers and owners. Evaluate of GMP and SSOP was carried out to see the effectiveness of conformity and non-conformity measures in carrying out the production process. The results of this study stated that the conformity assessment of the evaluation of the application of GMP and SSOP obtained a value of 42.50%-84.00%, with a deviation value of 185 from the overall value of 528 which means deviations in the moderate level so that the application of the GMP is said to be less in accordance with the provisions of the Regulation of the Minister of Industry No. 75 of 2010. The conformity assessment of the application of the SSOP obtained a value between 20.00%-84.00%, with a deviation value of 45 from the overall value of 160 which means that the deviation is in a moderate level or does not meet the FDA's provisions regarding SSOP as stated by government regulation, Number 28 of 2004 concerning food safety, quality, and nutrition. The high rate of deviations in the application of GMP and SSOP indicates a low level of contamination prevention during the production process.